Faktor Internal dan Eksternal Penentu Kesejahteraan Petani Jambu Mete di Desa Mata Kapore Kabupaten Sumba Barat Daya - Agnes Quartina Pudjiastuti; Yustina Sriyutun Saghu; Sumarno Sumarno (Jurnal Sosial Ekonomi Pertanian, 2021)
Indonesia's cashew export potential is quite large, but its value is still very low. The purpose of this study was to analyze the influence of internal and external factors on the welfare of cashew farmers. This research was conducted at the cashew production center, namely Mata Kapore Village, which is located in Kodi Bangedo District, Southwest Sumba Regency. Data was collected from 50 farmers using interview and observation methods. Farmers were selected by a simple random method. Data analysis used structural equation modeling (SEM) based on variance, namely Partial Least Square (PLS). External factors have a very significant effect on the welfare of farmers, either directly or indirectly through internal factors. Internal factors have no significant effect on farmers' welfare. To improve farmers' welfare, it is necessary to support access to capital and price guarantees for cashew farmers.